2017
DOI: 10.13189/ujm.2017.050103
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators, Barriers and Management Competencies Associated with Schools' Readiness to Implement New Accountable Practices

Abstract: Enrolling in the wake of an administrative and educational reform, the implementation of a new "results-based" management is shaking the schools' traditional values and practices, so the culture that characterizes them. In light of the results of three descriptive studies conducted with different groups of stakeholders concerned by this change, this text examines some of the main facilitators and barriers associated with schools' readiness to implement new regulation and evaluation practices. It also shed some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The difference between the two facilities was due to varying contextual factors and the availability of resources which was supported by the qualitative findings as well. This is consistent with two previous studies whereby intervention sites differed in readiness due to varying resource availability and reported contextual conditions such as past experiences in implementing programs per the specific setting [33]. It is worth discussing that our study’s approach of including facility staff plus supplemental qualitative accounts from different levels of management provided more detail on the varying conditions that lead to readiness as compared to Rubenstein et al’s study that indicated a limitation of only including reflections from facility leaders as a representation of the facilities [33].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The difference between the two facilities was due to varying contextual factors and the availability of resources which was supported by the qualitative findings as well. This is consistent with two previous studies whereby intervention sites differed in readiness due to varying resource availability and reported contextual conditions such as past experiences in implementing programs per the specific setting [33]. It is worth discussing that our study’s approach of including facility staff plus supplemental qualitative accounts from different levels of management provided more detail on the varying conditions that lead to readiness as compared to Rubenstein et al’s study that indicated a limitation of only including reflections from facility leaders as a representation of the facilities [33].…”
Section: Discussionsupporting
confidence: 92%
“…The difference in the studies is attributed to the main limitation of the inconsistency of constructs measured which may impact readiness to implement. For example, our study did not account for leadership whereas Rubenstein et al’s study used the CFIR framework which found the construct to be key in the non-readiness of facilities [33]. However, a review suggested that there is no gold standard in readiness studies as existing issues were tailored to specific studies, interventions and settings [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term readiness is intentional and refers to both the willingness and the ability of members in an organization (Lauzon, 2017;. Organizational readiness is also defined in terms of the organization's members' beliefs, attitudes, and intentions (Armenakis, Harris, & Mossholder, 1993).…”
Section: Cultural Readiness Factorsmentioning
confidence: 99%